2015
DOI: 10.1162/jocn_a_00784
|View full text |Cite
|
Sign up to set email alerts
|

Rescaling Retinal Size into Perceived Size: Evidence for an Occipital and Parietal Bottleneck

Abstract: The spatial and temporal context of an object influence its perceived size. Two visual illusions illustrate this nicely: the size adaptation effect and the Ebbinghaus illusion. Whereas size adaptation affects size rescaling of a target circle via a previously presented, differently sized adaptor circle, the Ebbinghaus illusion alters perceived size by virtue of surrounding circles. In the classical Ebbinghaus setting, the surrounding circles are shown simultaneously with the target. However, size underestimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This pattern of results suggests that the underestimation and the overestimation portions might be supported by different neural mechanisms. Considering that brain responses only in the visual cortex and parts of the parietal and the temporal regions were recorded (a limited number of channels were available for simultaneous recording), it is possible that the underestimation portion of the Ebbinghaus illusion engages critical neural processing in other brain regions (e.g., the frontal cortex; Kreutzer et al. 2015 ) than the recorded sites, which might account for the heritability observed with the behavioral underestimation effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern of results suggests that the underestimation and the overestimation portions might be supported by different neural mechanisms. Considering that brain responses only in the visual cortex and parts of the parietal and the temporal regions were recorded (a limited number of channels were available for simultaneous recording), it is possible that the underestimation portion of the Ebbinghaus illusion engages critical neural processing in other brain regions (e.g., the frontal cortex; Kreutzer et al. 2015 ) than the recorded sites, which might account for the heritability observed with the behavioral underestimation effect.…”
Section: Resultsmentioning
confidence: 99%
“…2013 ), the extrastriate cortex ( Frassinetti et al. 1999 ; Kreutzer et al. 2015 ), the lateral occipital complex ( Weidner and Fink 2007 ; Mancini et al.…”
Section: Introductionmentioning
confidence: 99%
“…Pooresmaeili, Arrighi, Biagi, & Morrone, 2013;Kreutzer, Fink, & Weidner, 2015;Laycock, Sherman, Sperandio, & Chouinard, 2017;Zeng, Kreutzer, Fink, & Weidner, 2017) have mainly addressed where in the visual pathway the size aftereffect emerges. But relatively few studies investigated the spatial aspects of the size adaptation (Kreutzer, Ralph, & Fink, 2015). Most critically, previous studies on size adaptation tested the perceptual effect always at the same visuospatial location as the adapter.…”
Section: Introductionmentioning
confidence: 99%
“…Functional magnetic resonance brain imaging studies have reported that the size of the activated area of V1 is related to the perceived rather than retinal size of a stimulus ( Murray, Boyaci, & Kersten, 2006 ; Pooresmaeili, Arrighi, Biagi, & Morrone, 2013 ; Sperandio, Chouinard, & Goodale, 2012 ). The lateral occipital cortex and the superior parietal cortex have also been implicated in illusory size perception ( Kreutzer, Weidner, & Fink, 2015 ; Plewan, Weidner, Eickhoff, & Fink, 2015 ; Shen, Zhang, & Chen, 2016 ; Zeng, Fink, & Weidner, 2020 ), with feedback projections to the early visual areas having been proposed to mediate the changes seen in early visual cortex ( Chen et al, 2019 ; Koivisto, Railo, Revonsuo, Vanni, & Salminen-Vaparanta, 2011 ; Zeng et al, 2020 ). Furthermore, there is some evidence that size aftereffects can transfer across space ( Altan & Boyaci, 2020 ; Corbett & Melcher, 2013 ), suggesting that additional mechanisms beyond primary visual cortex contribute to size perception.…”
Section: Introductionmentioning
confidence: 99%